The effects of cultural differences on social media behaviour - Guftométros, M.; Guerreiro, J. (International Journal of Internet Marketing and Advertising, 2021)
This paper studies the relationship between culture and social media marketing using Hofstede's cultural dimensions. The data were organically gathered from 6,750 posts from 225 different Facebook brand pages and 15 different countries. The gathered data included the engagement metrics such as the amount of likes, shares and comments and the various versions of likes such as love, wow and funny. Interesting differences were found that could be explained by Hofstede's dimensions. Countries low in individualism and/or high in power distance, share posts more than comments. Also the use of the funny and wow emoticon responses are related to higher scores on individualism. Findings from this paper show that the use of Hofstede's dimensions to group countries into different cultures predicts some online consumer behaviour patterns, particularly on Facebook.